Effect of Hydrogen on Grain Boundary Diffusion of Chromium in Zr–1 wt % Nb Alloy - Grabovskaya G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Kruglyakov M. A. Mark Aleksandrovich; Manisheva A. I. Anna Ildarovna (2025, 2025)
Title screen